2022
DOI: 10.1159/000525079
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Opioid Use Disorders Research by Integrating Multiple Data Modalities

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 92 publications
0
0
0
Order By: Relevance
“…11,12,16 The idea that a single domain of the EHR (e.g., ICD codes, laboratory values, clinical notes) can adequately yield a valid phenotype is increasingly gaining scrutiny. 20,22,23 The ABC instrument has historically been completed by clinicians to assess for risk of aberrant opioid use, with a threshold of 3 indicating potential inappropriate use; 1,24,25 however, some studies have used a threshold of 2 positive items to identify concerning opioid behaviors. 26,27 In this study, we found the best performance (based on F1 measures) was a threshold of 1.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,16 The idea that a single domain of the EHR (e.g., ICD codes, laboratory values, clinical notes) can adequately yield a valid phenotype is increasingly gaining scrutiny. 20,22,23 The ABC instrument has historically been completed by clinicians to assess for risk of aberrant opioid use, with a threshold of 3 indicating potential inappropriate use; 1,24,25 however, some studies have used a threshold of 2 positive items to identify concerning opioid behaviors. 26,27 In this study, we found the best performance (based on F1 measures) was a threshold of 1.…”
Section: Discussionmentioning
confidence: 99%